Extracellular conversion of adiponectin hexamers into trimers. Issue 6 (19th October 2012) - Kim, Jeong-a; Nuñez, Martha; Briggs, David B.; Laskowski, Bethany L.; Chhun, Jimmy J.; Eleid, Joseph K.; Quon, Michael J.; Tsao, Tsu-Shuen
Abstract : Adiponectin is an adipocyte-secreted hormone that exists as trimers, hexamers and larger species collectively referred to as HMW (high-molecular-weight) adiponectin. Whether hexamers or HMW adiponectin serve as precursors for trimers outside the circulation is currently unknown. Here, we demonstrate that adiponectin trimers can be generated from larger oligomers secreted from primary rat adipose cells or differentiated 3T3-L1 adipocytes. Purified hexameric, but not HMW, adiponectin converted into trimers in conditioned media separated from 3T3-L1 adipocytes or, more efficiently, when enclosed in the dialysis membrane in the presence of adipocytes. Several lines of evidence indicate that the conversion is mediated by an extracellular redox system. First, N-terminal epitope-tagged hexamers converted into trimers without proteolytic removal of the tag. Secondly, appearance of trimers was associated with conversion of disulfide-bonded dimers into monomers. Thirdly, thiol-reactive agents inhibited conversion into trimers. Consistent with a redox-based mechanism, purified hexamers reductively converted into trimers in defined glutathione redox buffer with reduction potential typically found in the extracellular environment while the HMW adiponectin remained stable. In addition, conversion of hexamers into trimers was enhanced by NADPH, but not by NADP + . Collectively, these data strongly suggest the presence of an extracellular redox system capable of converting adiponectin oligomers.